Retrospective analysis on distribution and antifungal susceptibility profile of Candida in clinical samples: a study from Southern India - S., Umamaheshwari; Sumana, M. N. (Frontiers in Public Health, 2023)
Introduction Candida is one of the rising primary causes of infections connected with health care. However, their distribution and susceptibility patterns vary widely amongst different regions. Method The study was carried out to retrospectively analyze the distribution of Candida in various clinical samples, their species types and susceptibility, in a tertiary care hospital, in India for 4 years using the Vitek-2 database. Results Candida infection was identified in 751 clinical samples, and the major source of infection was found to be urine samples accounting for about 58.32%. A total of 18 different Candida species were recorded. Non-albicans Candida (NAC) 73.64% (n = 553) predominated Candida albicans 26.36% (n = 198). Candida tropicalis was found to be identified at a higher frequency followed by C. albicans, Candida glabrata and Candida parapsilosis. Candida tropicalis was the only species which were recovered from bile; Candida pelliculosa was recorded merely from blood and Candida lipolytica from urine and blood and not in any other samples. In vaginal swabs, C. albicans accounted for 63.64% (n = 14) compared to NAC 36.36% (n = 8). The susceptibility test revealed that 75.44% (n = 559) isolates were susceptible and 24.56% (n = 182) were resistant to one or more drugs tested. Major resistance was exhibited to flucytosine by C. tropicalis 77.46% (n = 55) compared to C. albicans 11.27% (n = 8). Apart from C. albicans, NAC-C. tropicalis, C. glabrata and Candida krusei showed resistance to echinocandins, and Candida haemulonii to amphotericin-B. Conclusion The knowledge of the incidence, resistance and emergence of different species might guide clinicians to select an appropriate antifungal therapy and plan effective strategies to control invasive and systemic Candida infections.